Innovation in Administrative Services Through Sipersateng at the Regional Secretariat of Central Papua Province - Ellen Elsye; Amirul Mustofah; Aris Sunarya (International Journal of Humanities and Social Sciences Reviews, 2026)
This study analyzes the implementation of the Central Papua One-Stop Service Information System (Sipersateng) at the Central Papua Provincial Secretariat as a model for administrative innovation in the New Autonomous Region (DOB). The main focus of the study is to explore how a region with extreme infrastructure limitations can leapfrog or institutionalize towards an agile and transparent digital bureaucracy. Using a qualitative descriptive-analytical method with a case study approach, this research involved in-depth interviews, participant observation, and documentation studies to capture the dynamics of the transition from manual to digital systems. The results show that Sipersateng successfully reduced administrative process time by up to 60%. This success was driven by three main dimensions: institutional legitimacy through strong leadership commitment, technical resilience through offline-syncing features to address internet signal fluctuations, and significant changes in work culture. Adaptation strategies such as peer-mentoring methods for senior officials and mandatory policies through gubernatorial instructions proved effective in breaking down organizational cultural resistance. This study concludes that Sipersateng is not merely a technical tool, but rather a manifestation of Frontier Digital Bureaucracy that is able to mitigate the risk of maladministration and build public accountability in the newly formed province. This innovation demonstrates that geographic limitations are not a major barrier to achieving clean governance if supported by inclusive and adaptive system design. These findings provide a theoretical contribution to the public management literature on digitalization in regions with high structural challenges.